Gauging the acceptance of contact tracing technology: An empirical study of Singapore residents’ concerns with sharing their information and willingness to trust - Ong, Ee-Ing (Institutional Knowledge at Singapore Management University, 2022)
In response to the COVID-19 pandemic, governments began implementing various forms of contact tracing technology. Singapore’s implementation of its contact tracing technology, TraceTogether, however, was met with significant concern by its population, with regard to privacy and data security. This concern did not fit with the general perception that Singaporeans have a high level of trust in its government. We explore this disconnect, using responses to our survey (conducted pre-COVID-19) in which we asked participants about their level of concern with the government and business collecting certain categories of personal data. The results show that respondents had less concern with the government as compared to a business collecting most forms of personal data. Nonetheless, they still had a moderately high level of concern about sharing such data with the government. We further found that income, education and perceived self-exposure to AI are associated with higher levels of concern with the government collecting personal data relevant to contact tracing, namely health history, location and social network friends’ information. This has implications for Singapore residents’ trust in government collecting data and hence the success of such projects, not just for contact tracing purposes but for other government-related data collection undertakings.